Determination of destruction cause of experimental mill roll of stand roughing group of mill 150. - I. A. Guzova; N. A. Hodosovskaya; I. A. Kovaleva (Литьë и металлургия, 2021)
High quality of purchased resources plays a critical role under the conditions of severe international competition. Raw materials, materials and components are purchase for product production and their quality is an essential part in the production of steel at OJSC “BSW – Management Company of the Holding “BMC” holding». The problem of excessively high level of dynamic loads is especially acute for roughing stands. The main reasons for dynamic overloads are intense transient processes occurring in the rolling cycle, the presence of elastic constraints and gaps in the system, imperfection of electric drive system and errors made during development. Therefore, there is a need for selection of material and manufacturing technology for mill rolls capable to withstand such loads for a sufficiently long period. Investigations of destruction causes of experimental mill roll of stand roughing group of mill 150 of section rolling shop at OJSC “BSW – Management Company of the Holding “BMC” holding were carried out. Main classification features are established based on the analysis of the fracture. The results of metallographic studies of microstructure and chemical composition of central and subsurface zone roll fragments are presented. The reason of destruction of experimental mill roll was discovered – nonconformance of roll material grade with the requirements of technological instructions and normative documentation for rough group of stands No. 1–3